Gene expression patterns determine the differential numbers of dorsocentral macrochaetes between Musca domestica and Drosophila melanogaster. Issue 11 (30th December 2018) - Liang, Qing; Peng, Tingting; Sun, Boyuan; Tu, Jianbo; Cheng, Xingyi; Tian, Yuanliangzi; Fan, Xiaolan; Yang, Deying; Gaur, Uma; Yang, Mingyao
Abstract: The evolutionary differences in sensory bristle patterns on the thorax of dipterans are an excellent model for studying the patterns of evolutionary development. We observed that Drosophila melanogaster has two pairs of the large bristles, called macrochaetes, in the dorsocentral (DC) region of the notum, while Musca domestica retains six DC macrochaetes. To explore possible mechanism by which these two dipteran species have different numbers of DC bristles, we compared the corresponding protein sequences, the gene expression levels and the spatial expression patterns of five genes ( scute, pnr, ush, hairy, and emc ) for bristle development between two species. We also checked the overexpression of scute and emc in transgenic flies. The results demonstrated a strong conservation of five protein sequences between these two species. The mRNA expression of the five genes differed significantly between D. melanogaster and M. domestica . The gene expression patterns exhibited a species‐specific pattern during the larval development stage. It suggests that the function of these genes has been conserved in regulating the development of macrocheates between housefly and fruit fly, whereas the gene expression levels, especially spatial expression patterns lead to species‐specificity in DC bristles.